2014
DOI: 10.1186/1756-3305-7-113
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and histopathological detection of Hepatozoon canis in red foxes (Vulpes vulpes) from Portugal

Abstract: BackgroundHepatozoon canis is a protozoan tick-borne pathogen of dogs and wild canids. Hepatozoon spp. have been reported to infect foxes in different continents and recent studies have mostly used the polymerase chain reaction (PCR) for the detection and characterization of the infecting species. Surveying red foxes (Vulpes vulpes) may contribute to better understanding the epidemiology of canine vector-borne diseases, including hepatozoonosis caused by H. canis in domestic dogs. The present study investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 33 publications
3
37
1
2
Order By: Relevance
“…In our study, no significant difference was observed between a positive H. procyonis infection and the sex or age of the host. This information corroborates previous studies (Baneth et al 2013;Cardoso et al 2014;Aktas and Ozubek 2017) and suggests that coatis were infected when young. No association was observed between the H. canis infection in red foxes (Vulpes vulpes) and the sex or age of the animals, and the authors suggested that the foxes were infected by a vector or by transplacental transmission when young (Cardoso et al 2014).…”
Section: Discussionsupporting
confidence: 92%
“…In our study, no significant difference was observed between a positive H. procyonis infection and the sex or age of the host. This information corroborates previous studies (Baneth et al 2013;Cardoso et al 2014;Aktas and Ozubek 2017) and suggests that coatis were infected when young. No association was observed between the H. canis infection in red foxes (Vulpes vulpes) and the sex or age of the animals, and the authors suggested that the foxes were infected by a vector or by transplacental transmission when young (Cardoso et al 2014).…”
Section: Discussionsupporting
confidence: 92%
“…Hepatozoon canis infections can be diagnosed with blood smear examination for intracytoplasmic gamonts, histopathological examination for meronts and monozoic cysts in tissues (Baneth and Shkap, 2003), serological testing for anti-H. canis antibodies using an IFAT (Shkap et al, 1994) or an ELISA (Gonen et al, 2004), and PCR followed by Sanger sequencing of the 18S gene. PCR is a much more sensitive diagnostic method than blood smear examination alone, with studies reporting a ~3-5 fold increase in positive cases detected with PCR compared with blood smear examination (Karagenc et al, 2006;Otranto et al, 2011), and PCR is more sensitive than histopathology (Cardoso et al, 2014). At present, the only available genetic material for comparisons of this parasite are 18S sequences, and there are a variety of 18S primers that can be used for H. canis detection (Modry et al, 2017).…”
Section: Surveillance and Diagnostic Strategiesmentioning
confidence: 99%
“…H. felis has been the most frequently diagnosed species in cases of feline hepatozoonosis in different countries around the world [1,[9][10][11][12][13][14]. Interestingly, while some Hepatozoon species seem to be hostspecific, H. canis, the worldwide distributed Hepatozoon species infecting domestic dogs, is also able to infect cats [3,7,15,16] and several species of wild carnivores [17][18][19][20][21][22], which may represent an infection reservoir for domestic animals.…”
Section: Introductionmentioning
confidence: 99%